SYNTHESIS AND CHARACTERIZATION OF ZEOLITES FROM COAL FLY ASH WASTE - Fitriani, Mitra; Ramlan, Ramlan; Gunanto, Yohanes Edi; Setiawan, Jan (Indonesian Physical Review, 2025)
South Sumatra had coal production through PT Bukit Asam Tbk, which had coal production since 1950. Tanjung Enim Steam Power Plant (PLTU) is the largest coal ash producer because coal is the primary fuel. Coal combustion by-products include coal fly ash (CFA) and coal bottom ash (CBA). The current utilization of the CFA Tanjung Enim Steam Power Plant is for a cement mixture of PT Semen Baturaja and planting media. This work attempts to optimize zeolite synthesis from CFA by examining the effects of hydrothermal duration on reducing coal waste. This research studies the effect of hydrothermal time with time variations of 5, 12, and 24 on the morphology and phase of zeolite obtained. CFA from the Tanjung Enim Steam Power Plant contains SiO₂ and Al₂O₃, which account for 47.7% and 28.7% of the total composition, respectively. The SEM characterization result shows that the synthesized zeolite forms aggregates with a particle size of about 8-15 μm. Based on XRD characterization of CFA hydrothermal time of 5 hours, the dominant phase is the gibbsite phase, but there is a sodalite phase. The 12-hour hydrothermal time showed the formation of quartz, gibbsite, and sodalite phases. The 24-hour hydrothermal time shows that the dominant phase is sodalite, but there are gibbsite and quartz phases. The peak of the quartz phase decreases the longer the hydrothermal time. In this study, the duration of the hydrothermal process affects the formation of the zeolite phase.